2021
DOI: 10.1037/tra0001027
|View full text |Cite
|
Sign up to set email alerts
|

Institutional betrayal and help-seeking among women survivors of military sexual trauma.

Abstract: Women veterans experience disproportionately high rates of military sexual trauma (MST). Nonetheless, many MST survivors delay or forgo health care, particularly within Veterans Health Administration (VHA) settings. Institutional betrayal (IB) has been posited as a potential explanation for this. Objective: The current study examined if IB was associated with women veterans' willingness to seek VHA and non-VHA mental health and medical care, prior use of VHA care, past year use of VHA care, and use of VHA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…It is possible that discrimination, sexual harassment, and sexual assault, which is unfortunately overrepresented among female active duty personnel and veterans, 41,42 dissuade female veterans from seeking care in an institution (i.e., the VHA) that is viewed as an extension of the DoD. For instance, Monteith et al found that the construct of institutional betrayal was significantly predictive of women veteran MST survivors to endorse lower willingness to seek care from the VHA versus non‐VHA health care sources 43 . Previous research suggests that sexual minority female veterans are more likely than heterosexual female veterans to report histories of violence victimization 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that discrimination, sexual harassment, and sexual assault, which is unfortunately overrepresented among female active duty personnel and veterans, 41,42 dissuade female veterans from seeking care in an institution (i.e., the VHA) that is viewed as an extension of the DoD. For instance, Monteith et al found that the construct of institutional betrayal was significantly predictive of women veteran MST survivors to endorse lower willingness to seek care from the VHA versus non‐VHA health care sources 43 . Previous research suggests that sexual minority female veterans are more likely than heterosexual female veterans to report histories of violence victimization 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women Veterans are more likely to have trauma histories than non-Veterans, [ 13 ] and are at a higher risk of experiencing military sexual trauma (MST) than their men counterparts. [ 37 ] Women Veterans who have survived MST are less likely to seek treatment through the VHA, despite their eligibility, partly due to feelings of institutional betrayal – i.e., poor institutional response to MST may lead survivors to seek healthcare in civilian settings as opposed to identifying as a Veteran for the purposes of receiving healthcare through the VHA [ 37 ]. This may contribute to our findings that some providers believe they encounter few women Veterans with hazardous substance use.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the critical gap in the current literature, these findings can nonetheless help us advance the conceptual thinking around screening and hazardous substance use identification. Although we strategically targeted providers since screening and identification are systems-level issues, expanding this work to include more of the patient voice is warranted [ 37 ]. Future work to improve hazardous substance use screening and identification should further consider Veteran perspectives.…”
Section: Limitationsmentioning
confidence: 99%
“…One recent study of women veterans that did address barriers in the context of suicide prevention found that a history of military sexual assault was associated with lower willingness to use VHA care for mental health symptoms [41]. Relatedly, MST-related institutional betrayal may deter women veterans from seeking specific types of VHA care [42]. Given the association between institutional betrayal and suicide attempts [43], preventing and addressing institutional betrayal may be particularly important to increasing healthcare engagement and preventing suicide.…”
Section: Reducing Barriersmentioning
confidence: 99%